2017
DOI: 10.18298/ijlet.2034
|View full text |Cite
|
Sign up to set email alerts
|

The Eight Graders Writing Attitude toward Efl Writing in Indonesian Context

Abstract: The way the students feel about writing may affect how well they accomplish the writing task. To write well and to achieve the maximum performance in writing, the students need to have positive attitude toward it so that they can find solutions and strategies whenever they face writing problems. The purpose of the study is to describe the students' writing attitude toward writing in English and to find out their opinion and feeling toward writing. The present study uses mixed method design, by using survey to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the overall mean score shows that the learners' attitude toward writing skills is categorized as an optimistic view. This finding relates to the previous studies' results from (Setyowati, 2017), who found that their research participants' attitude toward writing in English was positive and moderate (82.12%). Then (Fadhilah et PANYONARA: Journal of English Education Vol.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the overall mean score shows that the learners' attitude toward writing skills is categorized as an optimistic view. This finding relates to the previous studies' results from (Setyowati, 2017), who found that their research participants' attitude toward writing in English was positive and moderate (82.12%). Then (Fadhilah et PANYONARA: Journal of English Education Vol.…”
Section: Discussionsupporting
confidence: 89%
“…If one lacks vocabulary, one will have problems in fully expressing themselves on writing [3]. Students must think about the concepts, the logical connections between the ideas, how the ideas are organized, the grammar, the word choice, and the writing features at the same time when producing a composition [4]. Even though a writer has a thorough outline, is aware of what to say, and has bookmarked the sources, he/she frequently struggles to convert the outline into a complete text [2].…”
Section: Introductionmentioning
confidence: 99%
“…A study on 55 senior high school students found that they had a positive attitude towards English [8]. Similarly, a study among 101 Senior High School students revealed that the students had a positive attitude towards English [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies revealed positive findings about Indonesian students" attitudes towards different aspects of English. The previous studies were conducted on small scales with a small number of participants, with [9] having the biggest participants (n= 101). In addition, none of these studies involved students from different universities.…”
Section: Introductionmentioning
confidence: 99%